Factors contributing to safe appendectomy in presence of appendiceal mass - Pandit, Rakesh Kumar; Gupta, Uma Shankar; Jha, Vinay Kumar; Magar, Subhash Thapa (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Early appendectomy in presence of appendiceal mass (AM) is controversial. We present the results of our experience that contribute to safe appendectomy in AM. Material and Methods: A total of 135 patients who underwent early surgery in presence of AM were reviewed. The diagnosis of AM was made clinically, using abdominal ultrasound and/or intra-operatively. All surgeries were done by qualified surgeons with variable experiences. Results: Mean operative day since onset of pain was 5.64 ± 2.1 (range: 3-15) days. A hundred and twenty patients underwent appendectomy, 116 (96.7%) of which was done within 7 days of pain. Two other patients operated on the 6th day had only drainage of abscess and no appendectomy. Remaining 4 (3.3%) appendectomies were performed on the 8th day. Two other patients operated on the 8th day had failed attempt of appendectomy and had just drainage of abscess. Two patients, operated on 12th and 15th day had just open-close. Both had given misleading history of duration of pain. Remaining 9 patients, from the 9th day onward underwent only just drainage of abscess. Only significant complication was injury to ileum during early years of experience when appendectomy was attempted on the 10th day. He fared well in two weeks. Conclusion: With experience we have developed confidence that experience and clarity of safe time limit makes early appendectomy in AM predictably safe. Few other patients who present later and need surgical intervention may be more safely managed by limited procedure like drainage of abscess without precarious attempt of appendectomy.